Desain Program Pelatihan - Zahratunnisa, Najwa; Septiani, Ira; Ikhsan, Eka Anwaril; Bachtiar, Machdum (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Rapid changes in the workplace, technological advancements, and increasing demands for human resource competencies require organizations to design training programs systematically and based on actual needs. However, many training programs are still implemented without a clear needs analysis, measurable objectives, and continuous evaluation, resulting in suboptimal impacts on performance improvement. This study aims to analyze the concept of effective training program design based on a literature review and to identify the key components that must be considered in its development, including training objectives and goals, materials and curriculum, learning methods and strategies, media and resources, as well as evaluation and follow-up. This research employs a qualitative approach using library research. Data were collected through the review of relevant books, scientific journal articles, and other academic sources, which were then analyzed systematically to identify principles for developing effective training programs. The findings indicate that the success of a training program is largely determined by an appropriate needs analysis, clearly defined and measurable objectives, relevant materials that integrate theory and practice, interactive and technology-adaptive learning methods, and adequate media and resources. Furthermore, continuous evaluation and follow-up are essential to ensure that training produces tangible improvements in competence and performance. Therefore, a systematic, well-planned, and needs-based training program design is proven to be more effective in supporting human resource development and organizational sustainability